Retraction Note: ANGPTL4 functions as an oncogene through regulation of the ETV5/CDH5/AKT/MMP9 axis to promote angiogenesis in ovarian cancer - Yinping Liu; Rui Yang; Yan Zhang; Yaping Zhu; Wei Bao (BMC, 2023)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s13048-022-01060-7.